2019
DOI: 10.3389/fphys.2019.01359
|View full text |Cite
|
Sign up to set email alerts
|

Post-activation Potentiation Versus Post-activation Performance Enhancement in Humans: Historical Perspective, Underlying Mechanisms, and Current Issues

Abstract: Post-activation potentiation (PAP) is a well-described phenomenon with a short half-life (~28 s) that enhances muscle force production at submaximal levels of calcium saturation (i.e., submaximal levels of muscle activation). It has been largely explained by an increased myosin light chain phosphorylation occurring in type II muscle fibers, and its effects have been quantified in humans by measuring muscle twitch force responses to a bout of muscular activity. However, enhancements in (sometimes maximal) volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
617
4
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 334 publications
(646 citation statements)
references
References 196 publications
(276 reference statements)
13
617
4
12
Order By: Relevance
“…Regardless of the mechanisms underpinning PAPE performance improvement, it can be speculated that the increase in time of the resistance effort could have been obtained as a result of increased muscle temperature and blood flow as well as water content following the CA. Thus, the PAPE protocol may contribute to enhancing the general effects of the warm-up [1]. Furthermore, the increase of TUT during the PAPE condition compared to the CONT (especially in third set) can also be attributed to increased phosphorylation of myosin light chains rendering the actin and myosin molecules more sensitive to Ca 2+ availability [5], which would allow the participants to maintain a certain amount of force even in the presence of biochemical changes within the working muscle that lead to fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the mechanisms underpinning PAPE performance improvement, it can be speculated that the increase in time of the resistance effort could have been obtained as a result of increased muscle temperature and blood flow as well as water content following the CA. Thus, the PAPE protocol may contribute to enhancing the general effects of the warm-up [1]. Furthermore, the increase of TUT during the PAPE condition compared to the CONT (especially in third set) can also be attributed to increased phosphorylation of myosin light chains rendering the actin and myosin molecules more sensitive to Ca 2+ availability [5], which would allow the participants to maintain a certain amount of force even in the presence of biochemical changes within the working muscle that lead to fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Athletic performance requires a high level of various training components that can be developed through a sports conditioning program. Recently, much attention has been given to acute increases in exercise performance through methods that induce a post-activation performance enhancement (PAPE) evoked by prior muscle activity [1]. PAPE has been defined as a physiological phenomenon which acutely improves voluntary muscular performance (e.g., jumps and throws) following a conditioning activity (CA) which includes a single heavy loaded resistance exercise [2][3][4] or consecutive sets of a single resistance exercise [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…suggested that "postactivation performance enhancement" be used when referring to the enhancement observed following voluntary contractions (Blazevich & Babault, 2019;Cuenca-Fernández et al, 2017). Therefore, this terminology will be used throughout when discussing voluntary contractions.…”
mentioning
confidence: 99%
“…In addition, there is some discussion that the enhancement in voluntary contraction could simply be the participant responding to a warm-up/familiarization with the movement rather than a response due to the classic local level mechanism (Blazevich & Babault, 2019).…”
mentioning
confidence: 99%
“…"Post-activation performance enhancement" (PAPE) is a new term introduced by Cuenca-Fernández et al [8] and describes such effects. In contrast to the classic post-activation potentiation, i.e., an increase in twitch force and power after electrically or voluntarily induced intense contraction [9,10], PAPE has a longer and weaker effect on performance, and is more likely attributed to different mechanisms [11]; the former is attributed to the phosphorylation of the myosin regulatory light-chain and the latter to changes in muscle temperature, muscle/cellular water content and/or muscle activation [11]. However, the acute effects of different conditioning stimuli-especially during warm-up-on the performance of tasks such as sprinting, is yet to be determined.…”
Section: Introductionmentioning
confidence: 85%